Internalisasi Pendidikan Agama Islam dan Budi Pekerti Dalam Mengembangkan Sikap Moderasi Beragama Melalui Materi Toleransi di SMA - Iha Hamidah (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This research is motivated by the fact that one way to foster bertasamuh is through Islamic Religious Education and Character Education which has an urgent role in shaping the character of students, an effort to meet the demands of the modern era where all elements of society are responsible for creating lasting peace. This research uses a qualitative approach with descriptive methods. Primary data source for Islamic Religious Education teachers. Secondary data: supporting books, journals and websites. Data collection techniques: observation, interviews and documentation. The research results show that: The internalization program is implemented in the form of daily programs, weekly programs, monthly and annual programs. Apart from the programs above, this was followed by several learning programs based on religious moderation which were included in the learning material in class, namely: Organizing corpses for class XI, Hajj, Zakat and Endowments for class dissemination of the moderation program to GPAI Bandung city. Meanwhile, implementation in developing an attitude of religious moderation is carried out through three processes, namely value transformation, value transaction and value transinteralization.